2020
DOI: 10.1111/jpy.12977
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Temperature, Irradiance, and pH on Teleaulax amphioxeia (Cryptophyceae) Physiology and Feeding Ratio For Its Predator Mesodinium rubrum (Ciliophora)1

Abstract: The cryptophyte Teleaulax amphioxeia is a source of plastids for the ciliate Mesodinium rubrum and both organisms are members of the trophic chain of several species of Dinophysis. It is important to better understand the ecology of organisms at the first trophic levels before assessing the impact of principal factors of global change on Dinophysis spp. Therefore, combined effects of temperature, irradiance, and pH on growth rate, photosynthetic activity, and pigment content of a temperate strain of T. amphiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…On the other hand, it was reported that G. cryophila was not negatively affected by high pCO 2 (Trimborn et al 2019; Camoying et al 2022), similar to what has been observed for cryptophytes in general when natural phytoplankton were grown under elevated pCO 2 levels (Sommer et al 2015; Schulz et al 2017; Donahue et al 2019). This is in line with the findings that cryptophytes are able to grow within a broad pH range (i.e., at both lower and upper extreme of the pH spectrum, Weisse and Stadler 2006; Gaillard et al 2020).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it was reported that G. cryophila was not negatively affected by high pCO 2 (Trimborn et al 2019; Camoying et al 2022), similar to what has been observed for cryptophytes in general when natural phytoplankton were grown under elevated pCO 2 levels (Sommer et al 2015; Schulz et al 2017; Donahue et al 2019). This is in line with the findings that cryptophytes are able to grow within a broad pH range (i.e., at both lower and upper extreme of the pH spectrum, Weisse and Stadler 2006; Gaillard et al 2020).…”
supporting
confidence: 89%
“…5C). Similar to the temperate cryptophyte Teleaulax amphioxeia (Gaillard et al 2020), G. cryophila was mainly influenced by temperature and irradiance and not by high pCO 2 . Based on our results, it becomes evident that the previously observed negative effects of high light alone on growth of the cryptophyte were alleviated by warming.…”
Section: Treatmentmentioning
confidence: 86%
“…Thus, this procedure may have increased their tolerance and performance to higher temperatures (Chakravarti et al, 2017). Gaillard et al (2020) found similar growth performances for T. amphioxeia in response to temperature. Thus, the combined assessment of our and other studies suggests that M. rubrum and its prey are tightly coupled in terms of thermal tolerance.…”
Section: Temperature Effects On Thermal Tolerance and Performancementioning
confidence: 82%
“…In the NE Atlantic (France) case study, the target for climate services was Dinophysis, a highly toxic HAB species, that even at low biomass can contaminate shellfish and cause shellfish poisoning if consumed by humans. For the natural scientists in this case, a key focus was on filling knowledge gaps on small scale ocean processes affecting the bloom and clarifying the adaptation of essential Dinophysis food web components to changing light, temperature and pH conditions (Gaillard et al, 2020). Knowledge at this small scale can be combined with physical oceanographic numerical modeling of future scenarios to progress climate service development (Ralston and Moore, 2020).…”
Section: Language and Terminologymentioning
confidence: 99%